Analisis Konsep Permintaan Konsumen dalam Perspektif Ekonomi Islam Terhadap Nilai Spiritual dalam Mempengaruhi Permintaan Konsumen - Nurma Maha Rani; Muhammad Givar Pamungkas; Salwa Ariza Irawan (Epsilon Journal of Management, 2025)
This study aims to analyze the concept of consumer demand in the perspective of Islamic economics with a focus on the influence of spiritual values ​​on the consumption behavior of Muslims. The academic problem underlying this study is the gap between the values ​​of Islamic teachings that emphasize simplicity, blessings, and spiritual responsibility, with the social reality of Muslims who often exhibit consumptive behavior and follow the flow of modern capitalism. This study uses a qualitative approach with library research methods, reviewing various literature related to the concept of consumption in Islamic economics, maqashid al-syari'ah, and spiritual values ​​such as halal, thayyib, qana'ah, wara', and zuhud. The results of the analysis show that spiritual values ​​have a significant role in shaping consumer demand that is not only oriented towards material satisfaction, but also towards blessings and social responsibility. Demand in Islamic economics is positioned as a moral and worship activity, not merely a rational economic decision. Consumption based on spiritual values ​​is also positively correlated with inner peace and mental health of consumers. Therefore, internalization of Islamic values ​​in consumption behavior is believed to be able to realize a fair, sustainable, and falah-oriented economic system (happiness in the world and the hereafter).